Effects of brown seaweeds on postprandial glucose, insulin and appetite in humans–a randomized, 3-way, blinded, cross-over meal study - Nazikussabah, Zaharudin; Tullin, Mikkel; Pekmez, Ceyda Tugba; Sloth, Jens J.; Rasmussen, Rie R.; Dragsted, Lars O. (Elsevier, 2021)
Seaweed including brown seaweeds with rich bioactive components may be efficacious for a glycaemic management strategy and appetite control. We investigated the effects of two brown edible seaweeds, Laminaria digitata (LD) and Undaria pinnatifida (UP), on postprandial glucose metabolism and appetite following a starch load in a human meal study. Methods: Twenty healthy subjects were enrolled in a randomized, 3-way, blinded cross-over trial. The study was registered under ClinicalTrials.gov Identifier no. NCT00123456. At each test day, the subjects received one of three meals comprising 30 g of starch with 5 g of LD or UP or an energy-adjusted control meal containing pea protein. Fasting and postprandial blood glucose, insulin, C-peptide and glucagonlike peptide-1 (GLP-1) concentrations were measured. Subjective appetite sensations were scored using visual analogue scales (VAS). Results: Linear mixed model (LMM) analysis showed a lower blood glucose, insulin and C-peptide response following the intake of LD and UP, after correction for body weight. Participants weighing 63 kg had a reduced glucose response compared to control meal between 40 and 90 min both following LD and UP meals. Furthermore, LMM analysis for C-peptide showed a significantly lower response after intake of LD. Compared to the control meal, GLP-1 response was higher after the LD meal, both before and after the body weight adjustment. The VAS scores showed a decreased appetite sensation after intake of the seaweeds. Ad-libitum food intake was not different three hours after the seaweed meals compared to control. Conclusions: Concomitant ingestion of brown seaweeds may help improving postprandial glycaemic and appetite control in healthy and normal weight adults, depending on the dose per body weight.